Engrosamiento endometrial en mujeres con sangrado postmenopáusico: correlación clínica por ecografía transvaginal e histopatología – Hospital Regional Docente de Trujillo. 2009 - 2013 - Asto Altamirano, Jorge Kevin (2016)
This study aimed to determine the correlation between endometrial thickness and detection of endometrial pathology in women with postmenopausal bleeding by using transvaginal ultrasound. MATERIAL AND METHOD: Descriptive, retrospective study, conducted in patients treated between 2009 and 2013 in the service of Gynecology of Hospital Regional Docente de Trujillo, which included 86 women with postmenopausal bleeding who underwent measurement of endometrial thickness by transvaginal ultrasound and endometrial biopsy. RESULTS: The histopathological findings were normal endometrium: 29.06%, endometrial atrophy: 16.27%, endometrial polyp: 11.63%, hyperplasia without atypia 23.25%, hyperplasia with atypia: 10.46%, endometrial carcinoma: 9.3%. Statistically significant correlation was found when they took <5 mm the value of endometrial thickness as a cutoff for identifying patients with normal endometrium (p = 0.012), and endometrial atrophy (p = 0.049); also, to the exclusion of pathologies as endometrial polyp (p = 0.045), hyperplasia without atypia (p = 0.030), hyperplasia with atypia (p = 0.025) and endometrial cancer (p = 0.024). CONCLUSION: There is a correlation between the assessment of endometrial thickness by transvaginal ultrasound and detection of endometrial pathology in women with postmenopausal bleeding when the endometrium is more than 5 millimeters